2023
DOI: 10.3390/ijms24076106
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Mitochondria and Natural Compounds Together in the Circle of Trust

Abstract: Human diseases are characterized by the perpetuation of an inflammatory condition in which the levels of Reactive Oxygen Species (ROS) are quite high. Excessive ROS production leads to DNA damage, protein carbonylation and lipid peroxidation, conditions that lead to a worsening of inflammatory disorders. In particular, compromised mitochondria sustain a stressful condition in the cell, such that mitochondrial dysfunctions become pathogenic, causing human disorders related to inflammatory reactions. Indeed, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…The development of oxidative stress also indicates the reduction of SOD2 and GPX1 subsequence decrease in the GSH/GSSG ratio in mitochondria [60]. Moreover, the progress of mitochondrial inflammation, indicated by the accumulation of carbonylated proteins [61], lack of mitochondrial ATP generation, and rising complex I activity level, is an indicator of a lack of mitochondrial metabolic functions, mitochondrial energetics, and antioxidant response [62,63]. In the present study, the exposure of IS (10 mg/L/hour/day; for 4 weeks) showed a significant (p < 0.05) reduction of BCO2, SOD2, and GPX1 activities along with a reduction in GSH/GSSG ratio and ATP contents.…”
Section: Effect Of Bc In Is-induced Renal Tissue Biomarker Changesmentioning
confidence: 97%
“…The development of oxidative stress also indicates the reduction of SOD2 and GPX1 subsequence decrease in the GSH/GSSG ratio in mitochondria [60]. Moreover, the progress of mitochondrial inflammation, indicated by the accumulation of carbonylated proteins [61], lack of mitochondrial ATP generation, and rising complex I activity level, is an indicator of a lack of mitochondrial metabolic functions, mitochondrial energetics, and antioxidant response [62,63]. In the present study, the exposure of IS (10 mg/L/hour/day; for 4 weeks) showed a significant (p < 0.05) reduction of BCO2, SOD2, and GPX1 activities along with a reduction in GSH/GSSG ratio and ATP contents.…”
Section: Effect Of Bc In Is-induced Renal Tissue Biomarker Changesmentioning
confidence: 97%
“…These two different pores are placed on the inner and outer mitochondrial membrane, respectively. The mtDNA released in the cytosol acts as a DAMP (damage-associated molecular pattern) molecule, activating the inflammasome and the cGAS-STING complex responsible for proinflammatory molecules, such as interleukin-1β and interleukin-18 and interferon signalling [ 61 , 62 ]. Thus, the antioxidant activities of UCP2 can revert the renal injury aggravated by lipopolysaccharide (LPS), counteracting the inflammation, macrophage infiltration, and the mitochondrial dysfunction linked to oxidative stress [ 35 ].…”
Section: Ucp2: a Possible Multifunctional Mitochondrial Carriermentioning
confidence: 99%
“…Accumulation of senescent cells due to accelerated aging and impaired removal leads to inflammation, a pathology encountered in sleep deprivation, severe mental illness and FTD [ 36 , 37 , 38 ]. Since mitochondria is a key driver of inflammation, dysfunction or loss of these organelles likely account for these pathologies [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%